Explorando la construcción social del cambio climático a través de redes semánticas naturales: un estudio sobre las perspectivas de los estudiantes universitarios - Cantú-Martínez, Pedro César (2023)
This research presents findings based on a study conducted among 84 university students in the field of life sciences. The study employed the methodology of natural semantic networks to explore the social construction of climate change. The results identified 70 words that are iconic representations of climate change. These words were ranked based on the frequency of their use by the university students, with the top five being alteration of rainfall, changes in flora and fauna, water scarcity, climatic variability, and the hole in the ozone layer. Together, these words accounted for 34.6% of the opinions obtained. The analysis also revealed that there was only a 6.25% difference in the semantic construct developed by men and women. Overall, the study highlights the potential of semantic networks as a tool for understanding how scientific and social representations of climate change are intertwined.